Priced literature: a bottleneck to wider applicability of scientific evidence - Bhandari, Parash Mani (Health for All, 2015)
With the advent of internet, scientific publishing has been less costly. Anyone at any corner of the world can benefit from the recent evidences generated by the scientific community, given that no mechanism to prevent such access exists. In practice, however, this huge potentiality of benefitting from science has been limited by the narrow paywall of academic publishers. This paper talks about the potential inhibitory effects priced literature can have on the applicability of scientific achievements and the latest activities aimed to discourage priced literature. These days, most of the journals are converting them from traditional subscription based model to new OA model, which is just a transformation from ‘pay-to-read’ to ‘pay-to-publish’ model. In countries like Nepal, where academic publishing hasn’t grown as a business, most of the journals are self-sustained with alternative mechanisms of funding the costs incurred. Health for All Vol.2 2014: 11-14